Experimental evaluation of solvent elution strength in reversed-phase TLC on medium polarity phases. Issue 9 (15th June 2019) - Komsta, Łukasz; Skibiński, Robert; Wróbel, Joanna; Gadowski, Sebastian; Skrzypiec, Karolina
Abstract: Seven chromatographic grade solvents miscible with water (acetone, acetonitrile, dioxane, ethanol, isopropanol, methanol, tetrahydrofuran), as well as water itself were investigated in the context of their eluotropic strength in reversed-phase chromatography on four medium-polar adsorbents (cellulose, CN, NH2 and DIOL). The test set for this research consisted of 35 model compounds. A modern chemometric mixture design concept allowed to estimate each solvent effect separately with a relatively small error (about 0.05 of RM value for all adsorbents). The solvent effects were analyzed chemometrically in multivariate manner and a final model was fitted to achieve the solvent strength. The estimation error was computed both from regression and bootstrap approach. GRAPHICAL ABSTRACT: